The Dangers of Being a Small, Oligotrophic and Light Demanding Freshwater Plant across a Spatial and Historical Eutrophication Gradient in Southern Scandinavia - Sand-Jensen, Kaj; Bruun, Hans Henrik; Nielsen, Tora Finderup; Christiansen, Ditte M.; Hartvig, Per; Schou, Jens C.; Baastrup-Spohr, Lars (Frontiers in Plant Science, 2018)
European freshwater habitats have experienced a severe loss of plant diversity, regionally and locally, over the last century or more. One important and well-established driver of change is eutrophication, which has increased with rising population density and agricultural intensification. However, reduced disturbance of lake margins may have played an additional key role. The geographical variation in water chemistry, which has set the scene for – and interacted with – anthropogenic impact, is much less well understood. We took advantage of some recently completed regional plant distribution surveys, relying on hundreds of skilled citizen scientists, and analysed the hydrophyte richness to environment relations in five contiguous South-Scandinavian regions. For three of the regions, we also assessed changes to the freshwater flora over the latest 50-80 years. We found a considerable variation in background total phosphorus concentrations and alkalinity, both within and between regions. The prevalence of functional groups differed between regions in accordance with the environmental conditions and the species’ tolerance to turbid waters. Similarly, the historical changes within regions followed the same trend in correspondence to the altered environmental conditions over time. Small submerged species decreased relative to tall submerged and floating-leaved species along the regional and historical eutrophication gradients. These changes were accompanied by systematically greater relative abundance of species of higher phosphorus prevalence. We conclude that species traits in close correspondence with anthropogenic impacts are the main determinants of local, regional and historical changes of species distribution and occupancy, while pure biogeography plays a minor role. Conservation measures, such as re-oligotrophication and re-established disturbance regimes through grazing and water level fluctuations, may help reduce the tall reed vegetation, restore the former richness of the freshwater flora and safeguard red-listed species, although extended time delays are anticipated in nutrient-rich regions, in which species only survive at minute abundance in isolated refugia.